Pengaruh Pengawasan dan Budaya Organisasi terhadap Kinerja Karyawan pada Anglo Eastern Plantation Group (Blankahan Eastern) - Ahmad Fadli; Debora Tambunan; Ade Pratama (Pusat Riset dan Inovasi Nasional, 2023)
This research aims to evaluate the performance of Anglo Eastern Plantation Group and specifically to test and analyze the effect of supervision on employee performance at Anglo Eastern Plantation Group (Blankahan Eastern). It also aims to test and analyze the effect of organizational culture on employee performance at Anglo Eastern Plantation Group (Blankahan Eastern) and to test and analyze the effect of supervision and organizational culture on employee performance at Anglo Eastern Plantation Group (Blankahan Eastern). The type of research used in this study is descriptive quantitative. The population used in this study consists of all employees at Anglo Eastern Plantation Group, totaling 221 individuals. The determination of the sample size was carried out using the Slovin formula, resulting in 142 individuals. The validity test was conducted using 30 respondents outside of the Anglo Eastern Plantation Group sample. The test results can be concluded that the supervision variable partially has a positive and significant effect on employee performance at Anglo Eastern Plantation Group. The organizational culture variable partially has a positive and significant effect on employee performance at Anglo Eastern Plantation. Supervision and Organizational Culture have an F-value of 86.441, which is greater than the F-table value of 3.07. This indicates that H0 is rejected and Ha is accepted, meaning that Supervision and Organizational Culture simultaneously and significantly affect employee performance at Anglo Eastern Plantation Group.